DEVELOPMENT OF MATHEMATICAL CRITICAL THINKING TEST INSTRUMENTS - Dzulfiqar Satria Waliyuddin; Dwi Sulisworo (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2021)
Improving the quality of education to encourage students to have 21st century abilities needs to be balanced with a test instrument that is able to measure students' 21st century abilities. The ability to think critically is one of the 21st century abilities that every student must have. Based on the indications, this study was carried out to create a test instrument capable of testing students' critical thinking skills. This research is classified as development research since it is based on the following stages of development: information collection, planning, initial product development, limited trial, initial product revision, field trial, and final product revision. Scale and comparison are the topics. In Sleman, Indonesia, 11th-grade students participated in the product testing. To establish a good category in general, product validity is based on expert opinion, item validity, discriminatory power, level of difficulty, and dependability.